From ego‐systems to open innovation ecosystems: A process model of inter‐firm openness. Issue 2 (1st March 2022) - Alam, Muhammad Aftab; Rooney, David; Taylor, Murray
Abstract: Existing innovation management literature significantly enhances our knowledge about " What " open innovation is and " Why " it is crucial for innovating superior products. However, very little is known about the process of " How " firms adopt openness. We engage in a qualitative exploratory study using a grounded theory method to understand the process by which firms open and migrate from ego‐systems to open innovation ecosystems. This paper reports on our findings from 3 rounds of 54 interviews with managers in the Macquarie Business Park, Australia. The first two rounds ( n  = 22 + 22) describe the openness process, define its qualitatively different phases, and detect critical variables that trigger or inhibit phase transition. In the final round ( n  = 10), member checks verify our interpretive model, revealing that inter‐firm openness occurs in four transitory phases—realization, socialization, strategic alignment, and two‐way openness. Phase transition starts somewhat spontaneously for firms but gets more complex as they proceed from ego‐system to an ecosystem, and the degree of openness increases in each subsequent phase. The study has significant theoretical and practical implications for product innovation management. Interdependence, social exchange, and trust play a significant role in creating open innovation ecosystems. Inter‐firm openness follows four interlocking transitory phases—realization, socialization, strategic alignment, and two‐way openness. Phase transitions start spontaneously but become complex as the degree of openness increases in subsequent phases.